Microbial colonization of microplastics in the Caribbean Sea. Issue 1 (6th January 2020) - Dudek, Kassandra L.; Cruz, Bianca N.; Polidoro, Beth; Neuer, Susanne
Abstract: Microplastics in the ocean function as an artificial microbial reef, with diverse communities of eukaryotic and bacterial microbiota colonizing its surface. It is not well understood if these communities are specific for the type of microplastic on which they develop. Here, we carried out a 6‐week long incubation experiment of six common plastic polymers in Bocas del Toro, Panama. The community composition of prokaryotes based on 16S rRNA gene sequencing data, when judged under a null model analysis, shows that neither plastic polymer type nor time exposed to the environment plays a significant role in shaping biofilm communities. However, the null model analyses of eukaryotic communities based on 18S rRNA gene sequences reveal that they can be significantly influenced by plastic polymer type and time incubated. This was confirmed by scanning electron microscopy, which allowed us to distinguish plastic‐specific diatom communities by the end of the incubation period.